ATTENTION IN TEACHING AND SCHOOL LEARNING - Milanković, Aleksandar (Metodička teorija i praksa, 2025)
In this paper, we examine the conceptualization of attention in the context of teaching and school learning. We start from the thesis that attention represents the fundamental framework that makes teaching and school learning possible, in general. In the paper, we first examine the exemplary theoretical definitions of attention, primarily in the perspective of pedagogy and psychology and then also from the point of view of contemporary philosophy. Furthermore, we examine the general value of attention in teaching and school learning, considering the key features of the teaching process and the problem of attention in teaching in general. Then, we examine the status of attention in the current Curriculum for grammar schools in the Republic of Serbia. Furthermore, we propose a simple didactic conceptualization of attention in teaching and school learning in four aspects, formed on the basis of characteristic conceptualizations of attention in traditional didactics and contemporary psychology and philosophy. Finally, we examine some of the important implications for teaching, teaching tools, methods, teaching content and school environment. In the paper, we propose the argument that articulating and cultivating attention should be one of the explicit, curricularly marked goals of the teaching process, since modern psychological and pedagogical research shows that attention is both 1) a condition for the teaching process and 2) one of the processes that itself is cultivated in the process. The theoretical framework of the work consists of traditional didactic, psychological and contemporary philosophical definitions of attention. First, the didactic conceptualization of attention in the didactics of Comenius, then the didactic conception of paying attention to exemplary phenomena by Martin Wagenschein, as well as contemporary pedagogical research into teaching and school learning as a process of forming attention - proposed by the author Johannes Rytzler. Second, contemporary psychological research and conceptualizations of attention. And finally, the theoretical framework of the work is made up of philosophical researches of the concept of attention, first of all, by the contemporary philosopher Sebastian Wetzl (Sebastian Watzl) - and his arguments on attention as a constitutive structure of consciousness given in the "center-periphery" model.
Keywords: attention; teaching; school learning; focus